2013
DOI: 10.1140/epjc/s10052-013-2337-6
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on spacetime anisotropy and Lorentz violation from the GRAAL experiment

Abstract: The GRAAL experiment could constrain the variations of the speed of light. The anisotropy of the speed of light may imply that the spacetime is anisotropic. Finsler geometry is a reasonable candidate to deal with the spacetime anisotropy. In this paper, the Lorentz invariance violation (LIV) of the photon sector is investigated in the locally Minkowski spacetime. The locally Minkowski spacetime is a class of flat Finsler spacetime and refers a metric with the anisotropic departure from the Minkowski one. The L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…All this phenomenology and cosmological constraints combined with particular QG theories where the effective geometry is Finslerian can give a better insight about LV and the colorful morphology of the physical manifold. This detailed and complicated analysis is an intriguing open challenge (for some recent studies see [91][92][93][94][95][96][153][154][155][156][157][158][159][160]). Since our amplification mechanism strongly depends on the intensity of Cartan tensor and its evolution in time, constraining the 'Finslerity' of space-time may lead to a better understanding of why our universe is magnetized.…”
Section: Discussionmentioning
confidence: 99%
“…All this phenomenology and cosmological constraints combined with particular QG theories where the effective geometry is Finslerian can give a better insight about LV and the colorful morphology of the physical manifold. This detailed and complicated analysis is an intriguing open challenge (for some recent studies see [91][92][93][94][95][96][153][154][155][156][157][158][159][160]). Since our amplification mechanism strongly depends on the intensity of Cartan tensor and its evolution in time, constraining the 'Finslerity' of space-time may lead to a better understanding of why our universe is magnetized.…”
Section: Discussionmentioning
confidence: 99%
“…[30]. This model suggested that the spacetime of very early universe may be of Randers-Finsler type.…”
Section: Primordial Power Spectra With Anisotropymentioning
confidence: 96%
“…We are only interested in the evolution of the very early universe. After our calculation of the connection and the curvature tensor, Einstein's gravitational equation could be obtained as [30,50] …”
Section: Primordial Power Spectra With Anisotropymentioning
confidence: 99%
See 2 more Smart Citations